Peranan PT. Sarana Pembangunan Palembang Jaya ( SP2J ) dalam Menyedikan Moda Transportasi di Kota Palembang - Sutinah Andaryani (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Abstract One indicator to see the economic development in a city, namely by looking at the transportation activities, especially land transportation and the pattern used by residents in one part of landuse (landuse). One part of landuse (landuse) in a city that can see the level and patterns of land transportation, namely in the